Ciclo estacional de Lepidosaphes ulmi (L.)(Hemiptera: Diaspididae) - Carrillo Ll, R.=700 1 Cifuentes C, C.; Mundaca B, N.
(Es, En)
Ilus., 13 ref.
Keywords: LEPIDOSAPHES; HEMIPTERA; DIASPIDIDAE; CICLO VITAL; DESARROLLO BIOLOGICO; CHILE; REVISTA CHILENA DE ENTOMOLOGIA